Effects of Anchored and Cognitive Flexibility Instructional Strategies on Secondary School Students’ Knowledge, Attitude and Practices in Biology in Ibadan,Nigeria (2015)
It has been observed that students have poor knowledge in Biology, a trend which is evident in performances in environmental concepts and the negative practices observed in their various classes. This has been attributed to non-usage of active and participatory instructional strategies which involve computer usage of powerpoint, hypertext, motion and sound presentations such as anchored and cognitive flexibility in teaching environmental concepts in Biology. Previous studies have investigated the efficacy of anchored instruction and cognitive flexibility strategies on students’ learning outcomes in Mathematics and Social studies but not in Biology. This study, therefore, determined the effects of anchored instructional strategy (AIS) and cognitive flexibility instructional strategy (CFIS) on senior secondary school (SS) students’ knowledge, attitude and practices in Biology in Ibadan, Nigeria. The moderating effects of gender and cognitive style were also determined. The pretest-posttest, control group, quasi-experimental design with 3x2x2 factorial matrix was adopted. Three senior secondary schools were purposively selected, each from Akinyele, Ibadan North and Ibadan North-West Local Government Areas. Four hundred and twenty three SS II students of intact classes participated in the study. Participants were assigned to experimental groups (AIS, CFIS), and control groups in each LGA, while the treatment lasted 12 weeks. Four validated instruments which included: Student’s Knowledge of Environmental Concept Test (r=0.83), Student Environmental Attitude Scale (r = 0.88), Student Perceived Environmental Practices Scale (r=0.82) and Cognitive Style Test (r=0.89) were used for data collection. Data were analysed using ANCOVA and Scheffe post- hoc at 0.05 level of significance. There was a significant main effect of treatment on students’ knowledge (F (2,421) = 403.31, ƞ2 =.66), attitude to (F(2,421) = 5.22, ƞ2 =.03) and practices (F(2,421) = 8.87, ƞ2 =.04) of environmental concepts in Biology. Participants in the AIS group had a higher knowledge mean score ( ̅ = 18.64) than those in the CFIS ( ̅ = 13.85) and control ( ̅ = 9.47) groups. Participants in the CFIS group had higher attitude mean score ( ̅ = 63.85) than those in the AIS ( ̅ = 63.13) and control ( ̅ = 61.62) groups. Also, students’ in AIS group had the highest mean score in environmental practices ( ̅ = 50.63), followed by CFIS ( ̅ = 48.15) and control group ( ̅ = 48.05). Cognitive style had a significant main effect on students’ environmental knowledge (F (1,422) = 3.97, ƞ2 = .01) and attitude to environmental concepts (F (1,242) = 9.32, ƞ2 = .02). The innovators had higher knowledge mean score ( ̅ = 14.25) than the adaptors ( ̅ = 13.73). The innovators had higher attitude mean score ( ̅ = 63.74) than the adaptors ( ̅ = 62.00). Gender had no significant main effect on students’ environmental knowledge, attitude and practices. There were no two-way and three-way interaction effects on environmental knowledge, attitude and practices. Anchored and cognitive flexibility instructional strategies enhanced students’ environmental knowledge, attitude and practices of students in Biology in Ibadan. Biology teachers and curriculum developers should adopt both instructional strategies to improve students’ learning outcomes regardless of gender in environmental concepts in Biology.